American honor the creation of the nation's ideals during the revolutionary era - Smith, Craig Bruce (University of North Carolina Press, 2018)
"...in the early eighteenth century, ideals of honor and virtue were salient aspects of Revolutionary Americans' ideological break from Europe and shared by all ranks of society, from the powdered-wig "founders" to college students, women, and African Americans. Focusing his study primarily on the prominent Americans who came of age before and during the Revolution...notably John Adams, Benjamin Franklin, Thomas Jefferson, and George Washington...Smith shows how a colonial ethical transformation became inseparable from the American Revolution, creating a continuing ethical ideology that still remains"...